Faktor-Faktor Penghambat Pertumbuhan Ikan Patin (Pangasius sp.) Yang Diberikan Pakan Buatan Pada Kolam Budidaya Dan Solusi Penanganannya - Cevin Winata Mendrofa (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Pangasius sp. is one of the leading freshwater aquaculture commodities in Indonesia with high economic value and growing market demand. The success of Pangasius culture is largely determined by optimal growth performance, which in practice is often hampered even when farmers provide artificial feed. This study aims to examine the factors inhibiting the growth of Pangasius sp. fed artificial feed in pond culture systems and to formulate appropriate management solutions. A descriptive qualitative method with a literature review approach was applied to national scientific articles published within the last ten years. The results indicate that growth-inhibiting factors include low quality and digestibility of artificial feed, fluctuating water quality (temperature, pH, dissolved oxygen, and ammonia), stocking densities that exceed pond carrying capacity, inadequate feeding management, and pest or disease attacks. Recommended solutions include supplementing feed with exogenous enzymes (papain and protease) to improve protein digestibility, applying biopore and biofloc technologies to stabilize water quality, adjusting stocking density and feeding frequency to growth stages, utilizing probiotics and photosynthetic bacteria, and diversifying natural and local feed sources. Integrated application of these solutions is expected to improve feed efficiency, growth rate, and survival of Pangasius sp. in pond culture systems.